α-Synuclein occurs in lipid-rich high molecular weight complexes, binds fatty acids, and shows homology to the fatty acid-binding proteins - Sharon, Ronit (The National Academy of Sciences, 2001)
α-Synuclein (αS) is a 140-residue neuronal protein that forms insoluble cytoplasmic aggregates in Parkinson's disease (PD) and several other neurodegenerative disorders. Two missense mutations (A53T and A30P) are linked to rare forms of familial PD. The normal function of αS is unknown, and cultured cell systems that model its modification from soluble monomers to aggregated forms have not been reported. Through a systematic centrifugal fractionation of mesencephalic neuronal cell lines and transgenic mouse brains expressing wild-type or A53T human αS, we observed unusual, previously unrecognized species of αS that migrate well above the 17-kDa monomeric form in denaturing gels. Incubation at 65°C of high-speed cytosols from cells or brains revealed a modified αS species migrating at ≈36 kDa and an extensive higher molecular mass αS-reactive smear. Extraction of the cytosols with chloroform/methanol or with a resin (Lipidex 1000) that binds fatty acids resulted in a similar pattern of higher molecular mass αS forms. On the basis of this effect of delipidation, we reexamined the primary structure of αS and detected a motif at the N and C termini that is homologous to a fatty acid-binding protein signature. In accord, we found that purified human αS binds oleic acid, with an apparent K(d) of 12.5 μM. We also observed an enhanced association of A53T αS with microsomal membranes in both mesencephalic cells and transgenic mouse brains. We conclude that αS has biochemical properties and a structural motif that suggest it is a novel member of the fatty acid-binding protein family and may thus transport fatty acids between the aqueous and membrane phospholipid compartments of the neuronal cytoplasm.